Precocity and fruit characteristics of mangosteen sprayed with urea and muriate of potash under Sulu conditions - Arakama, Nursima K.; Oria, Demetrio P. (2011)
The study aimed to assess the effects of urea and muriate of potash on precocity of mangosteens under Sulu conditions. The effects of once and two monthly applications of the foliar fertilizers were evaluated. Results indicate that application of foliar solutions of urea or muriate of potash twice a month gave rise to the direct effect in promoting growth in terms of length and circumference of shoots. Muriate of potash at 200 and 300 g per 16 liters water produced more flowers, high flowering intensity, and gave high fruit set and retention in mangosteens. Moreover, it enhanced development stages resulting in higher yield per tree with good quality of fruits. Result clearly demonstrated lesser disease reaction which is another trait of trees that is attributed to the improved nutrient status of crops. No physiological disorders of some common diseases were found. Foliar feeding of mangosteen trees with urea an muriate of potash tended to have caused reduction in the incidence of these diseases.
Keywords: Mangosteen; Foliar Fertilization; Mindanao studies